MALAY TRADITIONAL FERMENTED FOOD: WILL MILLENNIALS EAT IT? - Norfezah Md Nor; Anis Syafiqah Kamaruddin (Journal of Islamic, Social, Economics and Development, 2021)
Globalization and modernization are dynamic factors that influenced the millennials to consume Malay traditional fermented food. Thus, this may lead to the challenge in creating awareness towards sustainability of Malay traditional fermented food and avoid the possibility of losing the value of food heritage among millennials. In addressing this issue, this study was conducted to examine the behavioral intention in consuming the Malay traditional fermented food among millennials. An extended Theory of Planned Behavior (TPB) with modification was employed in this study. A quantitative e-survey was conducted through google form platform. The collected data of 131 millennial respondents were then analyzed with a descriptive statistic followed by correlation and multi regression using SPSS 21 version. The result showed all factors including attitude (r=0.542, p=0.00), subjective norm (r=0.585, p=0.00), perceive behavior control (r=0.40, p=0.651) and neophobia (r=0.214, p=0.014) have a positive significant relationship towards intention to consume Malay traditional fermented food among millennials. However, the multiple regression result revealed only three predictors explained 37.0% of the variance (R2=0.383, F (3,127) =26.308, p<0.0005), which indicate 63% factors that influence the millennials behavioral towards the intention to consume Malay traditional fermented food were also contributed by others factors. These results are expected to highlight the significance of millennials generation’s role as an agent in continuing towards sustaining the Malay traditional fermented food against the globalization and modernization. Hence, this may have a positive impact on the traditional food business and tourism food heritage industry sustainability.